VALIDITAS PREDIKTIF HASIL BELAJAR DI SEKOLAH LANJUTAN TINGKAT ATAS, NILAI EBTANAS MURNI, DAN SKOR UJIAN MASUK KE PERGURUAN TINGGI TERHADAP KEBERHASILAN BELAJAR DI PERGURUAN TINGGI - Sentot Soelistyo, - (1993)
Seledting potential candidates to be admitted to a university is a pivotal decision making process. High-learning institutions often face various problems in admitting their candidates. The fact shows that the number of candidates who want to study at the university is more than the university capability to admit them. Therefore it is necessary to create a selection mechanism that can select the best candidates who will be predictively able to complete their study punctually. A good selection mechanism will increase the efficiency of the university. Although efforts have been made by the government to find out an appropriate selection system, the efforts seemed to be a never ending process. This can be noticed with the changing of the selection system used, started in 1977 with the ,introduction of selection model used by the five excellent universities: University of Indonesia (UI), Bandung Institute of Technology (ITB), Bogor Institute of Agriculture (IPB), Gadjah Mada University (UGM), and Airlangga University (UNAIR). They worked together to create the university entrance examinations which then called SKALU (Joint-Secretariat of Five Excellent University). In later development, SKALU became Pilot Project I through Pilot Project V in 1978. However, in 1984 all the selection models were integrated to be a single model which was then popular as SIPENMARU (Admittance Selection for New Students), along with its special programme called PMDK (Talent scouting for un iversity students). Since 1989 SIPENMARU has been changed to UMPTN (State-run University Entrance Tests) model, which is now still implemented.